Combining physical vapor deposition structuration with dealloying for the creation of a highly efficient SERS platform - Chauvin, Adrien; Puglisi, Walter; Thiry, Damien; Satriano, Cristina; Snyders, Rony; Bittencourt, Carla (Beilstein Journal of Nanotechnology, 2023)
Nanostructured noble metal thin films are highly studied for their interesting plasmonic properties. The latter can be effectively used for the detection of small and highly diluted molecules by the surface-enhanced Raman scattering (SERS) effect. Regardless of impressive detection limits achieved, synthesis complexity and the high cost of gold restrict its use in devices. Here, we report on a novel two-step approach that combines the deposition of a silver–aluminum thin film with dealloying to design and fabricate efficient SERS platforms. The magnetron sputtering technique was used for the deposition of the alloy thin film to be dealloyed. After dealloying, the resulting silver nanoporous structures revealed two degrees of porosity: macroporosity, associated to the initial alloy morphology, and nanoporosity, related to the dealloying step. The resulting nanoporous columnar structure was finely optimized by tuning deposition (i.e., the alloy chemical composition) and dealloying (i.e., dealloying media) parameters to reach the best SERS properties. These are reported for samples dealloyed in HCl and with 30 atom % of silver at the initial state with a detection limit down to 10−10 mol·L−1 for a solution of rhodamine B.
Keywords: dealloying; magnetron sputtering; nanoporous thin film; nanostructuring; SERS

(untitled) - Chi, H.; Wang, C.; Wang, Z.; Zhu, H.; Mesias, V. S. D.; Dai, X.; Chen, Q.; Liu, W.; Huang, J. (Analyst, 2020)

(untitled) - Langer, J.; Jimenez de Aberasturi, D.; Aizpurua, J.; Alvarez-Puebla, R. A.; Auguié, B.; Baumberg, J. J.; Bazan, G. C.; Bell, S. E. J.; Boisen, A.; Brolo, A. G.; Choo, J.; Cialla-May, D.; et al. (ACS Nano, 2020)

(untitled) - Hu, X.; Wang, X.; Ge, Z.; Zhang, L.; Zhou, Y.; Li, J.; Bu, L.; Wu, H.; Li, P.; Xu, W. (Analyst, 2019)

(untitled) - Liyanage, T.; Rael, A.; Shaffer, S.; Zaidi, S.; Goodpaster, J. V.; Sardar, R. (Analyst, 2018)

(untitled) - Bruzas, I.; Lum, W.; Gorunmez, Z.; Sagle, L. (Analyst, 2018)

(untitled) - Chauvin, A.; Lafuente, M.; Mevellec, J. Y.; Mallada, R.; Humbert, B.; Pina, M. P.; Tessier, P.-Y.; El Mel, A. (Nanoscale, 2020)

(untitled) - Koklioti, M. A.; Bittencourt, C.; Noirfalise, X.; Saucedo-Orozco, I.; Quintana, M.; Tagmatarchis, N. (ACS Appl. Nano Mater., 2018)

(untitled) - Ha Pham, T. T.; Dien, N. D.; Vu, X. H. (RSC Adv., 2021)

(untitled) - Pettinger, B.; Wenning, U.; Wetzel, H. (Surf. Sci., 1980)

Surface-Enhanced Raman Scattering: Physics and Applications - Kneipp, K.; Moskovits, M.; Kneipp, H. (Springer, 2006)

(untitled) - Moskovits, M. (J. Chem. Phys., 1978)

(untitled) - Hexter, R. M.; Albrecht, M. G. (Spectrochim. Acta, Part A, 1979)

(untitled) - Jun Yin, H.; Yang Chen, Z.; Mei Zhao, Y.; Yang Lv, M.; An Shi, C.; Long Wu, Z.; Zhang, X.; Liu, L.; Li Wang, M.; Jun Xu, H. (Sci. Rep., 2015)

(untitled) - Mcmahon, M. D.; Lopez, R.; Meyer, H. M., III; Feldman, L. C.; Haglund, R. F., Jr (Appl. Phys. B: Lasers Opt., 2005)

(untitled) - Fan, M.; Andrade, G. F. S.; Brolo, A. G. (Anal. Chim. Acta, 2011)

(untitled) - Yin, G.; Bai, S.; Tu, X.; Li, Z.; Zhang, Y.; Wang, W.; Lu, J.; He, D. (Nanoscale Res. Lett., 2019)

Nanoporous Gold: From an Ancient Technology to a High-Tech Material - Wittstock, A.; Biener, J.; Erlebacher, J.; Bäumer, M. (Royal Society of Chemistry, 2012)

(untitled) - Cintra, S.; Abdelsalam, M. E.; Bartlett, P. N.; Baumberg, J. J.; Kelf, T. A.; Sugawara, Y.; Russell, A. E. (Faraday Discuss., 2006)

(untitled) - Zamuner, M.; Talaga, D.; Deiss, F.; Guieu, V.; Kuhn, A.; Ugo, P.; Sojic, N. (Adv. Funct. Mater., 2009)

(untitled) - El Mel, A.-A.; Stephant, N.; Hamon, J.; Thiry, D.; Chauvin, A.; Chettab, M.; Gautron, E.; Konstantinidis, S.; Granier, A.; Tessier, P.-Y. (Nanoscale, 2016)

(untitled) - El Mel, A.-A.; Chettab, M.; Gautron, E.; Chauvin, A.; Humbert, B.; Mevellec, J.-Y.; Delacote, C.; Thiry, D.; Stephant, N.; Ding, J.; Du, K.; Choi, C.-H.; et al. (J. Phys. Chem. C, 2016)

(untitled) - McCue, I.; Benn, E.; Gaskey, B.; Erlebacher, J. (Annu. Rev. Mater. Res., 2016)

(untitled) - Erlebacher, J. (J. Electrochem. Soc., 2004)

(untitled) - El Mel, A.-A.; Boukli-Hacene, F.; Molina-Luna, L.; Bouts, N.; Chauvin, A.; Thiry, D.; Gautron, E.; Gautier, N.; Tessier, P.-Y. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Chen, L.-Y.; Yu, J.-S.; Fujita, T.; Chen, M.-W. (Adv. Funct. Mater., 2009)

(untitled) - Zhang, L.; Liu, H.; Chen, L.; Guan, P.; Chen, B.; Fujita, T.; Yamaguchi, Y.; Iwasaki, H.; Xue, Q.-K.; Chen, M. (RSC Adv., 2016)

(untitled) - Zhang, T.; Sun, Y.; Hang, L.; Li, H.; Liu, G.; Zhang, X.; Lyu, X.; Cai, W.; Li, Y. (ACS Appl. Mater. Interfaces, 2018)

(untitled) - Rajput, A.; Kumar, S.; Singh, J. P. (Analyst, 2017)

(untitled) - Jonker, D.; Jafari, Z.; Winczewski, J. P.; Eyovge, C.; Berenschot, J. W.; Tas, N. R.; Gardeniers, J. G. E.; De Leon, I.; Susarrey-Arce, A. (Nanoscale Adv., 2021)

(untitled) - Matikainen, A.; Nuutinen, T.; Itkonen, T.; Heinilehto, S.; Puustinen, J.; Hiltunen, J.; Lappalainen, J.; Karioja, P.; Vahimaa, P. (Sci. Rep., 2016)

(untitled) - Gragg, J. E., Jr; Cohen, J. B. (Acta Metall., 1971)

(untitled) - McAlister, A. J. (Bull. Alloy Phase Diagrams, 1987)

(untitled) - Alexander, K. B.; Legoues, F. K.; Aaronson, H. I.; Laughlin, D. E. (Acta Metall., 1984)

(untitled) - Thornton, J. A. (J. Vac. Sci. Technol., A, 1986)

(untitled) - Alvarez, R.; García-Martín, J. M.; Macías-Montero, M.; Gonzalez-Garcia, L.; González, J. C.; Rico, V.; Perlich, J.; Cotrino, J.; González-Elipe, A. R.; Palmero, A. (Nanotechnology, 2013)

(untitled) - Mukherjee, S.; Gall, D. (Thin Solid Films, 2013)

(untitled) - Chauvin, A.; Horak, L.; Duverger-Nédellec, E.; Dopita, M.; Tessier, P.-Y.; El Mel, A.-A. (Surf. Coat. Technol., 2020)

(untitled) - Niauzorau, S.; Sharstniou, A.; Sampath, V. K.; Kublik, N.; Bandarenka, H.; Azeredo, B. (ACS Appl. Mater. Interfaces, 2022)

(untitled) - Chauvin, A.; Txia Cha Heu, W.; Tessier, P.-Y.; El Mel, A.-A. (Phys. Status Solidi B, 2016)

(untitled) - Sieradzki, K.; Corderman, R. R.; Shukla, K.; Newman, R. C. (Philos. Mag. A, 1989)

(untitled) - Li, L.; Zhu, Y.-J. (J. Colloid Interface Sci., 2006)

(untitled) - Luechinger, N. A.; Walt, S. G.; Stark, W. J. (Chem. Mater., 2010)

(untitled) - Wang, X.; Qi, Z.; Zhao, C.; Wang, W.; Zhang, Z. (J. Phys. Chem. C, 2009)

(untitled) - Qian, L. H.; Yan, X. Q.; Fujita, T.; Inoue, A.; Chen, M. W. (Appl. Phys. Lett., 2007)

(untitled) - Bittencourt, C.; Hecq, M.; Felten, A.; Pireaux, J. J.; Ghijsen, J.; Felicissimo, M. P.; Rudolf, P.; Drube, W.; Ke, X.; Van Tendeloo, G. (Chem. Phys. Lett., 2008)

(untitled) - Sun, S.; Sun, Y.; Liu, Z.; Lee, D.-I.; Peterson, S.; Pianetta, P. (Appl. Phys. Lett., 2006)

(untitled) - Song, T.; Gao, Y.; Zhang, Z.; Zhai, Q. (CrystEngComm, 2011)

(untitled) - Qiu, H.; Zhang, Z.; Huang, X.; Qu, Y. (ChemPhysChem, 2011)

(untitled) - Hildebrandt, P.; Stockburger, M. (J. Phys. Chem., 1984)

(untitled) - Zhang, X.; Xiao, X.; Dai, Z.; Wu, W.; Zhang, X.; Fu, L.; Jiang, C. (Nanoscale, 2017)

(untitled) - Shahine, I.; Mevellec, J.-Y.; Richard-Plouet, M.; Humbert, B.; Tessier, P.-Y. (J. Phys. Chem. C, 2022)

(untitled) - Wu, N.; Gao, W.; Lian, Y.; Du, J.; Tie, X. (Food Chem., 2017)

(untitled) - Fang, C.; Agarwal, A.; Buddharaju, K. D.; Khalid, N. M.; Salim, S. M.; Widjaja, E.; Garland, M. V.; Balasubramanian, N.; Kwong, D.-L. (Biosens. Bioelectron., 2008)

(untitled) - Kumar, E. A.; Wang, T.-J.; Chang, Y.-H. (Appl. Surf. Sci., 2022)

(untitled) - Huang, J.-A.; Zhang, Y.-L.; Zhao, Y.; Zhang, X.-L.; Sun, M.-L.; Zhang, W. (Nanoscale, 2016)

(untitled) - Xu, B.-B.; Zhang, Y.-L.; Zhang, W.-Y.; Liu, X.-Q.; Wang, J.-N.; Zhang, X.-L.; Zhang, D.-D.; Jiang, H.-B.; Zhang, R.; Sun, H.-B. (Adv. Opt. Mater., 2013)

(untitled) - Zhang, R.; Xu, B.-B.; Liu, X.-Q.; Zhang, Y.-L.; Xu, Y.; Chen, Q.-D.; Sun, H.-B. (Chem. Commun., 2012)

(untitled) - Schneider, C. A.; Rasband, W. S.; Eliceiri, K. W. (Nat. Methods, 2012)